ANALISIS PERANCANGAN USAHA PRODUK PEMILAH SAMPAH ORGANIK DAN ANORGANIK MODERN - putra, festo renza ardhana (JUSTI (Jurnal Sistem dan Teknik Industri), 2023)
In designing product design, the purpose of making modern waste bins for organic and non-organic sorting is to overcome waste management problems in Indonesia. By looking at these problems, we strive to create innovations so that people can understand a good way to manage waste. The product to be developed is a trash can with an automatic sorting sensor system, allowing the selection of waste one by one. by using the Economic Order Quantity method aims to assist companies in overcoming the problem of controlling raw material inventory Economic Order Quantity. Research shows that the manufacture of modern trash cans involves several steps, such as attention to product images, quality, size, and durability. Another strategy involves determining prices after market research to find prices that match consumer needs and wants. From these calculations, the production of modern trash cans can be considered feasible and beneficial to society, can help reduce littering and minimize piles of garbage. This modern waste separator product is expected to provide great benefits to the community and become a valuable learning.